Hyponatraemic convulsion secondary to desmopressin treatment for primary enuresis. - Apakama, D C (1999)
The case of a 6 year old child who presented with convulsions and coma after unsupervised self administration of intranasal desmopressin (DDAVP) for nocturnal enuresis is presented. Children with enuresis can be embarassed by their condition and may believe that multiple doses of their nasal spray may bring about a rapid resolution. Water intoxication is an uncommon but serious adverse effect of treatment with intranasal DDAVP. These patients may present with seizure, mental state changes, or both. Basic management consists of stopping the drug, fluid restriction, and suppressive treatment for seizures. Recovery is usually rapid and complete. Administration of the nasal spray in children should be supervised by parents to prevent highly motivated children from accidental overdose. The risks of high fluid intake need to be carefully explained to both parents and children.